Effects of surfaces nanocrystallization induced by shot peening on material properties : a Review - Sara Bagheri Fard; Mario Guagliano (Fracture and Structural Integrity)
A brief description of surface nanosrystallization process via severe plastic deformation is presented. To come to the point different shot peening methods which have proved to be able to create nanocrystalline layers are demonstrated clarifying the actual state of the art. Then the influence of the process is reviewed on material behavior and a wide range of affected properties are investigated. On this basis some possible addresses for future research in this field are drawn and underlined.